Ultra-capacitors in power conversion systems : applications, analysis and design from theory to practice - Grbovic, Petar J. (Chichester, West Sussex, United Kingdom : John Wiley & Sons Ltd., 2014)
"Divided into five parts, this book is focused on ultra-capacitors and their applications in power conversion systems. It discusses ultra-capacitor analysis, modelling and module design from a macroscopic (application) perspective. It also describes power conversion applications, interface dc-dc converter design and entire conversion system design. Part One covers the background of energy storage technologies, with particular attention on state-of-the-art ultra-capacitor energy storage technologies. In Chapter four of this part, power conversion systems with integrated energy storage is discussed. The advantages and disadvantages of the use of ultra-capacitors versus electrochemical battery energy storage in particular applications are clearly identified. Part Two covers system design aspects in detail, and Part Three is dedicated to a case study of controlled electric drive applications. A case study of renewable energy and power quality applications is presented throughout Part Four. Part Five focuses on a case study of diesel-electric hybrid applications, such as autonomous generators, heavy tracks, dampers and earth moving equipment. Each part includes end-of-chapter design examples and exercises, discussion of the topic, design procedure, and a presentation of the different control schemes for the topic"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Electric current converters -- Equipment and supplies; Supercapacitors; Electric machinery -- Equipment and supplies; TECHNOLOGY & ENGINEERING / Power Resources / General; Electronic books